Gender differences in integral indicators of adaptation of athletes’ bodies to training in different energy modes - Tnimova, G.T.; Bodeev, M.T.; Kuznetsova, L.S. (Karagandy University of the name of academician E.A. Buketov, 2025)
Adaptation to intense muscle activity leads to an increase in athletic performance. The task is not to bring an athlete to the stage of failure of adaptation mechanisms during training, which is accompanied by a drop in performance and other negative consequences, hence the need to have accessible and informative markers of the athlete’s body condition in order to correct the training process. The study was conducted at the Olympic Training Center (OTC), city of Karaganda. The participants were athletes without health complaints. To determine the physical performance of athletes, a submaximal PWC 170 test was used, and the MOC was calculated by an indirect method. Based on the measurement of the main indicators of the cardiovascular system (HR, SBP, DBP) and the calculation of derivative indices (PP, SBV, MCV, DP, KEC) adopted in sports medicine and adaptology (ShI, IFC), a comparative analysis of the adaptation of the body of high-class athletes (46 people) to training in different energy modes (aerobic, anaerobic-aerobic, anaerobic) was performed. The study showed differences in the adaptation indicators of the cardiovascular system of the athletes depending on the energy mode of training and gender. Measurement and subsequent calculation of accessible and informative indicators of adaptation of the cardiovascular system of the athlete’s body to training loads in different energy modes allows not only to monitor its current state, but also to identify the stress preceding the breakdown of adaptation mechanisms.
Keywords: athlete; gender; energy training regime; cardiovascular system adaptation; stress; adaptation failure; indices